Bioengineered Carboxymethylcellulose–Peptide Hybrid Nanozyme Cascade for Targeted Intracellular Biocatalytic–Magnetothermal Therapy of Brain Cancer Cells - Alexandra A. P. Mansur; Sandhra M. Carvalho; Luiz Carlos A. Oliveira; Elaine Maria Souza-Fagundes; Zelia I. P. Lobato; Maria F. Leite; Herman S. Mansur (Pharmaceutics, 2022)
Glioblastoma remains the most lethal form of brain cancer, where hybrid nanomaterials biofunctionalized with polysaccharide peptides offer disruptive strategies relying on passive/active targeting and multimodal therapy for killing cancer cells. Thus, in this research, we report for the first time the rational design and synthesis of novel hybrid colloidal nanostructures composed of gold nanoparticles stabilized by trisodium citrate (AuNP@TSC) as the oxidase-like nanozyme, coupled with cobalt-doped superparamagnetic iron oxide nanoparticles stabilized by carboxymethylcellulose ligands (Co-MION@CMC) as the peroxidase-like nanozyme. They formed inorganic–inorganic dual-nanozyme systems functionalized by a carboxymethylcellulose biopolymer organic shell, which can trigger a biocatalytic cascade reaction in the cancer tumor microenvironment for the combination of magnetothermal–chemodynamic therapy. These nanoassemblies were produced through a green aqueous process under mild conditions and chemically biofunctionalized with integrin-targeting peptide (iRDG), creating bioengineered nanocarriers. The results demonstrated that the oxidase-like nanozyme (AuNP) was produced with a crystalline face-centered cubic nanostructure, spherical morphology (diameter = 16 ± 3 nm), zeta potential (ZP) of −50 ± 5 mV, and hydrodynamic diameter (DH) of 15 ± 1 nm. The peroxide-like nanostructure (POD, Co-MION@CMC) contained an inorganic crystalline core of magnetite and had a uniform spherical shape (2R = 7 ± 1 nm) which, summed to the contribution of the CMC shell, rendered a hydrodynamic diameter of 45 ± 4 nm and a negative surface charge (ZP = −41 ± 5 mV). Upon coupling both nanozymes, water-dispersible colloidal supramolecular vesicle-like organic–inorganic nanostructures were produced (AuNP//Co-MION@CMC, ZP = −45 ± 4 mV and DH = 28 ± 3 nm). They confirmed dual-nanozyme cascade biocatalytic activity targeted by polymer–peptide conjugates (AuNP//Co-MION@CMC_iRGD, ZP = −29 ± 3 mV and DH = 60 ± 4 nm) to kill brain cancer cells (i.e., bioenergy “starvation” by glucose deprivation and oxidative stress through reactive oxygen species generation), which was boosted by the magneto-hyperthermotherapy effect when submitted to the alternating magnetic field (i.e., induced local thermal stress by “nanoheaters”). This groundwork offers a wide avenue of opportunities to develop innovative theranostic nanoplatforms with multiple integrated functionalities for fighting cancer and reducing the harsh side effects of conventional chemotherapy.